The Compleat observer? : a field research guide to observation - Sanger, Jack (Qualitative studies series ; E-Book, 1996)
Combining anecdotal accounts, inter-professional experiences, critical debate and practical pointers to being a good observer, this book explores issues surrounding observation in social science-orientated research.